Durability of Springs - Kobelev, Vladimir; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book offers an advanced treatise of the mechanics of springs with focus on the springs for automotive industry. It demonstrates new and original results for the optimization of helical springs as well the design of disk springs and thin-walled springs and presents the new results for creep and relaxation of springs made of steel under high static loads. The fatigue of springs and weak link concept for cyclically loaded springs are enlightened. The closed form solutions of advanced problems allow the deeper understanding of spring mechanics and optimization of energy harvesters.
Introduction -- Principles of Spring Design -- Stress Distribution over Cross-Section of Wire -- "Equivalent Column" Model for Helical Springs -- Coiling Process for Helical Springs -- Disk Springs -- Creep and Relaxation of Springs -- Generalization of Creep Laws for Spring Materials -- Fatigue of Spring Materials -- Failure Probabilty of Helical Spring -- Thin-Walled Rods with Semi-Opened Profiles -- Semi-Opened Profiles for Twist-Beam Automotive Axles -- Appendices.
Keywords: Automotive engineering; Materials -- Analysis; Mechanics, Applied; Solids; Automobile industry and trade; Automotive Engineering; Characterization and Analytical Technique; Solid Mechanics; Automotive Industry